Human rights and comparative foreign policy - Forsythe, David P. (United Nations University Press, 2003)
Human rights and comparative foreign policy is the first book in english to examine the place of human rights in the foreign policies of a wide range of states during contemporary times. The book is also unique in utulizing a common framework of analysis for all 10 of the country or regional studies covered. This framework treats foreign policy as the result of a two-level game in which both domestic and foreign factors have to be considered.